A unified approach for univalent functions with negative coefficients using the Hadamard product - Assiri, E. Q.; Mogra, M. L. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
For given analytic functions ϕ(z) = z + Σ n=2 ∞ λ n z n , Ψ(z) = z + Σ n=2 ∞ μ with λ n ≥ 0, μ n ≥ 0, and λ n ≥ μ n and for α, β (0≤α